Impact of temperature on the isothermal adsorption/desorption of shale gas - Wei GUO; Wei XIONG; Shusheng GAO; Zhiming HU; Honglin LIU; Rongze YU (Petroleum Exploration and Development, 2013)
Isothermal adsorption and desorption experiments under different temperatures were carried out with the Longmaxi Formation shale samples collected from southern Sichuan. The experimental results show that temperature affects the adsorption and desorption capacity of shale, the adsorption capacity of shale decreases with temperature increase. The adsorption curve and desorption curve of shale are not coincident and the thermodynamic reason for the hysteresis of the desorption curve is that the isosteric heat of the shale adsorption process is greater than that of the desorption process. The Langmuir model and desorption model can describe the isothermal adsorption and desorption processes very well, respectively. Isothermal adsorption and desorption curves under different temperatures can be predicted by isosteric heat curves which match the experimental results. Shale gas production is a process of gas desorption and the desorption characteristics directly impact the production of shale gas, so the desorption model should be taken into consideration in the shale gas production forecast and numerical simulation. Key words: shale, temperature, adsorption, desorption, isosteric adsorption heat